自适应多载波滤波器响应系统和方法 (2022)
本主题涉及一种在无线频分双工系统中提供可编程滤波器响应的设备、系统和方法。特别地，在一些实施例中，用于这样的系统的可调谐同向双工滤波器包括：第一可调谐滤波器，其在输入节点和第一输出节点之间通信，第一可调谐滤波器可调谐成限定第一可调谐通带，所述第一可调谐通带被配置为在高于第一阻带的频率处具有最小通带插入损耗；以及第二可调谐滤波器，其在输入节点与第二输出节点之间通信，所述第二可调谐滤波器可调谐成限定第二可调谐通带，所述第二可调谐通带被配置为在低于第一阻带的频率处具有最小通带插入损耗。 The present subject matter relates to devices, systems, and methods that provide a programmable filter response in a wireless frequency division duplex system. In particular, in some embodiments, a tunable diplex filter for such a system includes a first tunable filter in communication between an input node and a first output node, the first tunable filter being tunable to define a first tunable pass band configured to have a minimum pass band insertion loss at frequencies that are higher than a first reject band, and a second tunable filter in communication between the input node and a second output node, the second tunable filter being tunable to define a second tunable pass band configured to have a minimum pass band insertion loss at frequencies that are lower than t